Caught on the web. - Isakson, Carol (Education Digest, 2001)
Presents several Web sites for teachers of mathematics. Portals of EDinformatics; Features of PBS Teacher Source Math; Collection of java applets created by Jacobo Bulaevsky at the Educational Java Programs site; Web virtual library maintained by the Florida State University.